Prevalence, risk factors, and antimalarial resistance patterns of falciparum plasmodiasis among pregnant women in Kaduna metropolis, Nigeria - Maryam Muhammad Aliyu; Idris Abdullahi Nasir; Yahaya Abdullahi Umar; Anthony Philip Vanstawa; Jessy Thomas Medugu; Anthony Uchenna Emeribe; Dele Ohinoyi Amadu (Tzu Chi Medical Journal)
Objective: Pregnant women infected with malaria represent a significant obstetric problem, especially in the face of antimalarial resistance. This cross-sectional study investigated the prevalence of malaria parasitemia, associated risk factors as well as the antimalarial resistance pattern of Plasmodium isolates from pregnant women attending four selected secondary health facilities in Kaduna State, Nigeria. Materials and Methods: Blood samples were collected from 353 pregnant women attending selected hospitals. Malaria microscopy and parasite density count were conducted based on standard protocols. Antimalarial susceptibility test (using chloroquine, artesunate, artether, and sulfadoxine-pyrimethamine), and hemoglobin concentrations were determined using schizont maturation assay and methemoglobin method, respectively. Multiple-drug resistance (MDR) was defined by resistance against ≥3 antimalarial drugs. Results: The overall prevalence of plasmodiasis was 22.4%. Out of those infected, 5.2% was found to be anemic. Malaria parasitemia was significantly associated with parity, residential area, age of women, and use of preventive measures against malaria (P < 0.05) but not with hemoglobin concentration, occupation, and trimester of pregnancy (P > 0.05). Malaria parasites from the pregnant women exhibited the highest resistance against chloroquine, 75 (94.9%) followed Artemether, 30 (37.9%) then sulfadoxine-pyrimethamine, 29 (36.7%) and least resistant to artesunate, 28 (35.4%). The prevalence of MDR was 40.5% (32/79). Conclusion: The prevalence of malaria was relatively high due to inadequate and/or ineffective preventive measures adopted by pregnant women. More so, significant isolates of Plasmodium falciparum exhibited MDR against antimalarial agents tested.